2017
DOI: 10.1021/acssuschemeng.7b00842
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Hierarchically Structured Cellulose@ZnO Composite in Solid–Liquid Homogeneous Phase: Synthesis, DFT Calculations, and Enhanced Antibacterial Activities

Abstract: To explore the interactions of nanoparticles and bioresources and elucidate their effects on the morphology of the resulting composite, hierarchically structured cellulose@ZnO composites have been synthesized by an environmentally friendly hydrothermal method in one step. First, self-assembly induces the formation of hierarchical three-level structures, including cellulose/ZnO nanofibers, layers, and microfibers. Then, ZnO microparticles deposit onto the surface of the third-level cellulose/ZnO microfibers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…A hierarchically structured cellulose@ZnO composite was found the enhanced antibacterial activities with diameters of the inhibition zone were found to be 48.8 and 45.5 mm against the S. aureus and the E. coli , respectively. It is indicated that the cellulose@ZnO composite material can be utilized to improve food packaging materials . CuO nanoparticles impregnated bacterial cellulose and chitosan nanofibers were fabricated to enhance the antibacterial activity for food packing applications.…”
Section: Introductionmentioning
confidence: 99%
“…A hierarchically structured cellulose@ZnO composite was found the enhanced antibacterial activities with diameters of the inhibition zone were found to be 48.8 and 45.5 mm against the S. aureus and the E. coli , respectively. It is indicated that the cellulose@ZnO composite material can be utilized to improve food packaging materials . CuO nanoparticles impregnated bacterial cellulose and chitosan nanofibers were fabricated to enhance the antibacterial activity for food packing applications.…”
Section: Introductionmentioning
confidence: 99%
“…In low pH conditions, small ZnO particles are found on the surface of cellulose (Figure 2a-c); increase the pH to 12, ZnO microparticles about 300 nm length and 50 nm width are observed (Figure 2d). According to a previous study, ZnO nanoparticles with certain sizes are easily to selfassemble with cellulose [30]. However, in this study, we didn't find the same size ZnO nanoparticles on prepared cellulose composite.…”
Section: Fe-sem Tem and Eds Analysismentioning
confidence: 64%
“…Cellulose@ZnO composite was prepared by the hydrothermal method used in previous research [30]. 3.0 g zinc acetate and 1.0 g cellulose were dissolved in 25 mL distilled water.…”
Section: Preparation Of Cellulose@znomentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial efficacy of this nanocomposite has shown to be dependent on the concentration of zinc oxide nanoparticles in the composition. Studies have demonstrated that as the amount of zinc oxide increases, the antibacterial activity also increases (Yu et al, 2014;Zhao et al, 2017). Quantitative analysis of the minimum inhibitory concentration (MIC) of zinc oxide-cellulose nanocomposites revealed that the MIC for S. aureus is 0.44 mg/mL -1 , whilst for E. coli it is 0.63 mg/mL -1 (Zhao et al, 2017).…”
Section: Zinc Oxide -Cellulosementioning
confidence: 99%